Integration for inclusion in early childhood education. Sustainable educational approaches for children with Autism Spectrum Disorders - Galdieri, Michela; Zappalà , Emanuela; Aiello, Paola (Formazione & insegnamento, 2021)
Promoting an inclusive culture is one of the goals to be pursued towards a concept of sustainability based on the principles of participation and self-determination of all pupils. Due to the heterogeneity of its manifestations, children on the Autism Spectrum Disorder require educational interventions that favour effective communication and interaction from early childhood. This paper proposes a reflection on an integrated intervention model in the educational field, which includes the inclusive potential of the Group-Based Early Start Denver Model (G-ESDM) and the use of strategies and tools of Alternative and Augmentative Communication (AAC). The aim is to set up learning environments that encourage the full participation of children with ASD by giving all educators and/or teachers an active role as facilitators of communication, inclusive and learning processes.